The possible mediating relationship promoted by the self-efficacy of breastfeeding associated with the Kangaroo Method on indicators of exclusive breastfeeding - Rayany Cristina de Souza; Paula Carolina Bejo Wolkers; Leandro Alves Pereira; Rejane Sousa Romão; Eliziane Santos Medeiros; Daniela Marques de Lima Mota Ferreira; Ana Elisa Madalena Rinaldi; Vivian Mara Gonçalves de Oliveira Azevedo (Elsevier, 2022)
Objective: Assess the mediating role of breastfeeding self-efficacy in the association between the Kangaroo Neonatal Intermediate Care Unit and exclusive breastfeeding. Method: Cross-sectional study nested in a cohort, carried out in the Neonatal Unit of a Brazilian university hospital between September 2018 and March 2020. The sample consisted of 114 newborns weighing ≤1800 g and their mothers who were divided into those who participated in the first and second stages of the Kangaroo Method and those who only passed through the first stage, categorized as the Conventional group. To assess the self-efficacy of breastfeeding, the Breastfeeding Self Efficacy Scale - Short-Form was used. The Mann-Whitney test was used to compare the breastfeeding self-efficacy score between the groups, and Fisher's exact test to compare rates of exclusive breastfeeding. The adjusted structural equation model was used to check for the mediating effect of breastfeeding self-efficacy. The significance level adopted was 5%. Results: The kangaroo group had a higher rate of exclusive breastfeeding at hospital discharge (p = 0.000). There was a positive association between having remained in the kangaroo (p = 0.003) and the breastfeeding self-efficacy score (p = 0.025) with the rate of exclusive breastfeeding at hospital discharge. Breastfeeding self-efficacy did not act as a mediator. Conclusion: The self-efficacy of breastfeeding and the stay of the low birth weight newborn baby in the kangaroo unit acted positively and independently in exclusive breastfeeding, and the self-efficacy of breastfeeding did not act as a mediator in this association.